The potential for give and take in plant–microbiome relationships - Lebeis, Sarah L. (Frontiers in Plant Science, 2014)
Mutualistic microbes present in plant-associate microbial communities provide a variety of benefits for their host, including reciprocal exchange of nutrients and/or protection from biotic and abiotic environmental stresses. Plant microbiomes have remarkably robust composition in comparison to the complex and dynamic microbial environments from which they form, suggesting finely-tuned discrimination by the plant host. Here the intersection between the plant immune system and microbiomes will be explored, both as a possible means of shaping community membership and as a consequence elicited by certain colonizing microbes. Notably, the advent of massive parallel sequencing technologies allows the investigation of these beneficial microbial functions within whole community settings, so we can now ask how engagement of the immune response influences subsequent microbial interactions. Thus, we are currently poised for future work defining how the plant immune system impacts microbiomes and consequently host health, allowing us to better understand the potential of plant productivity optimization within complex microbial surroundings.